GM3 Ganglioside Linked to Neurofibrillary Pathology in a Transgenic Rat Model for Tauopathy - Olešová, Dominika; Majerová, Petra; Hájek, Roman; Piešťanský, Juraj; Brumarová, Radana; Michalicová, Alena; Jurkanin, Bernadeta; Friedecký, David; Kováč, Andrej (International journal of molecular sciences, 2021)
Glycosphingolipids (GSLs) are amphipathic lipids composed of a sphingoid base and a fatty acyl attached to a saccharide moiety. GSLs play an important role in signal transduction, directing proteins within the membrane, cell recognition, and modulation of cell adhesion. Gangliosides and sulfatides belong to a group of acidic GSLs, and numerous studies report their involvement in neurodevelopment, aging, and neurodegeneration. In this study, we used an approach based on hydrophilic interaction liquid chromatography (HILIC) coupled to high-resolution tandem mass spectrometry (HRMS/MS) to characterize the glycosphingolipid profile in rat brain tissue. Then, we screened characterized lipids aiming to identify changes in glycosphingolipid profiles in the normal aging process and tau pathology. Thorough screening of acidic glycosphingolipids in rat brain tissue revealed 117 ganglioside and 36 sulfatide species. Moreover, we found two ganglioside subclasses that were not previously characterized-GT1b-Ac2 and GQ1b-Ac2. The semi-targeted screening revealed significant changes in the levels of sulfatides and GM1a gangliosides during the aging process. In the transgenic SHR24 rat model for tauopathies, we found elevated levels of GM3 gangliosides which may indicate a higher rate of apoptotic processes.
Keywords: Tauopathies; mozek; Chromatography, Liquid; mass spectrometry; Humans; Acidic Glycosphingolipids; neurofibrily; Hydrophobic and Hydrophilic Interactions; geneticky modifikovaná zvířata; kyselé glykosfingolipidy; tau Proteins; sulfoglykosfingolipidy; stárnutí; liquid chromatography; krysa rodu Rattus; lidé; zvířata; G(M3) Ganglioside; Aging; Sulfoglycosphingolipids; proteiny tau; glycosphingolipids; Animals, Genetically Modified; gangliosides; chromatografie kapalinová; Brain; tauopathy; Rats; Neurofibrils; Animals; neurodegeneration; G(M3) gangliosid; tauopatie; Disease Models, Animal; aging; hydrofobní a hydrofilní interakce; sulfatides; modely nemocí na zvířatech